Development of a resonant excitation coil of AC magnetometer for evaluation of magnetic fluid - Mohd Mawardi, Saari; Nazatul Sharreena, Suhaimi; Saifudin, Razali; Nurul Akmal, Che Lah; Sakai, Kenji; Kiwa, Toshihiko; Tsukada, Keiji (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
A high-homogeneity excitation coil with a resonant circuit for AC magnetometer is developed. A solenoid coil is designed to produce a high-homogeneity and strong excitation field using a resonant frequency method. The solenoid coil is fabricated with a Litz wire to suppress the increase of AC resistance due to the skin and proximity effects in the high-frequency region. The Litz wire is composed of 60 strands of copper wires with 0.1-mm diameter. The resonant frequency method is applied to cancel the reactance component by connecting the excitation coil with a capacitor in a series configuration. To enable excitation of the magnetic field at multiple frequencies, a resonant circuit consists of multiple values of resonant capacitors is constructed. The fabricated excitation coil showed a high homogeneity of the magnetic field and was able to maintain a constant resonant current up to 32.5 kHz.